2020
DOI: 10.1101/2020.03.07.20031393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The epidemiological characteristics of 2019 novel coronavirus diseases (COVID-19) in Jingmen, Hubei, China

Abstract: Findings: Of the 213 cases (108 men and 105 women) , 88 (41%) had exposure to Wuhan. The median age was 48 years ( range,2-88 years;IQR,35-58.5). Thirty-three severe patients with a median age of 66 years(range,33-82 years,IQR, 57-76) were treated in intensive care units; out of these patients, 66.7 %(22) were men and 19 (57.5%) had chronic diseases, including hypertension, diabetes, heart failure, stroke, and renal insufficiency. Under the controlled measures, the number of new patients gradually decreased an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…31 studies [17-20, 23-25, 27-50] were performed in China and 3 studies [21,22,26] were conducted in Italy, France, and Korea. 23 studies published in English and 11 studies [40][41][42][43][44][45][46][47][48][49][50] published in Chinese. The sample size per study ranged from 28 to 1,591 and the total sample size was 8,080 (4,867 males, 3,213 females).…”
Section: General Characteristics and Quality Of Studiesmentioning
confidence: 99%
“…31 studies [17-20, 23-25, 27-50] were performed in China and 3 studies [21,22,26] were conducted in Italy, France, and Korea. 23 studies published in English and 11 studies [40][41][42][43][44][45][46][47][48][49][50] published in Chinese. The sample size per study ranged from 28 to 1,591 and the total sample size was 8,080 (4,867 males, 3,213 females).…”
Section: General Characteristics and Quality Of Studiesmentioning
confidence: 99%
“…In the present study, the investigation of the epidemiology and clinical symptoms of COVID-19 patients revealed that, consistent with previous reports, patients with severe disease were older than those with nonsevere disease. This may be related to the weakening of the body's defense system caused by the declination of immune function or the presence of underlying diseases (e.g., hypertension, chronic renal failure, and diabetes mellitus) in elderly patients [6][7][8] [12] . Therefore, clinicians should closely monitor the disease progression of middle-aged and elderly patients to avoid missing the optimal treatment time.…”
Section: Discussionmentioning
confidence: 99%
“…An outbreak of 2019 novel Coronavirus diseases (COVID-19) that began in Wuhan, China has now escalated to a worldwide pandemic (1)]. Individuals infected with COVID-19 experience mild to moderate respiratory illnesses, but often recover without requiring special treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals infected with COVID-19 experience mild to moderate respiratory illnesses, but often recover without requiring special treatment [2]. Symptoms of COVID-19 can include fever, cough, difficulty breathing and pneumonia in both lungs [1]. Older adults and those with underlying health disorders and medical problems such as cardiovascular and respiratory diseases, diabetes and cancer are more likely to have a more severe form of illness [2].…”
Section: Introductionmentioning
confidence: 99%